PREVALENCE OF HYPERGLYCEMIA AND ARTERIAL HYPERTENSION IN HIV-INFECTED POPULATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
According to statistics, CHD has been the leading cause of death in many economically developed countries of the world for many years. They are rightly called the epidemic of the 20th century.